Age‐related variation in non‐breeding foraging behaviour and carry‐over effects on fitness in an extremely long‐lived bird. (20th June 2018) - Clay, Thomas A.; Pearmain, Elizabeth J.; McGill, Rona A. R.; Manica, Andrea; Phillips, Richard A.
Abstract: Senescence has been widely documented in wild vertebrate populations, yet the proximate drivers of age‐related declines in breeding success, including allocation trade‐offs and links with foraging performance, are poorly understood. For long‐lived, migratory species, the non‐breeding period represents a critical time for investment in self‐maintenance and restoration of body condition, which in many species is linked to fitness. However, the relationships between age, non‐breeding foraging behaviour and fitness remain largely unexplored. We performed a cross‐sectional study, investigating age‐related variation in the foraging activity, distribution and diet of an extremely long‐lived seabird, the wandering albatross Diomedea exulans, during the non‐breeding period. Eighty‐two adults aged 8–33 years were tracked with geolocator‐immersion loggers, and body feathers were sampled for stable isotope analysis. We tested for variation in metrics of foraging behaviour and linked age‐related trends to subsequent reproductive performance. There was an age‐related decline in the number of landings (a proxy of foraging effort) during daylight hours, and a decrease in body feather δ 13 C values in older males but not females, yet this did not accompany an age‐related shift in distributions. Males conducted fewer landings than females, and the sexes showed some spatial segregation, with males foraging further south, likely due to their differential utilization of winds. Although younger (<20 years) birds had higher foraging effort, they all went on to breed successfully the following season. In contrast, among older (20+ years) birds, individuals that landed more often were more likely to defer breeding or fail during incubation, suggesting they have lower foraging success. As far as we are aware, this is the first demonstration of an age‐specific carry‐over effect of foraging behaviour in the non‐breeding period on subsequent reproductive performance. This link between foraging behaviour and fitness in late but not early adulthood indicates that the ability of individuals to forage efficiently outside the breeding period may be an important driver of fitness differences in old age. A plain language summary is available for this article. Abstract : Plain Language Summary